2016
DOI: 10.1016/j.cej.2015.09.087
|View full text |Cite
|
Sign up to set email alerts
|

The formation of haloacetamides and other disinfection by-products from non-nitrogenous low-molecular weight organic acids during chloramination

Abstract: Low-molecular weight organic acids (LMWOAs) are widespread in nature, and many are recalcitrant during conventional drinking water treatment, due to their LMW and hydrophilic character. This study assessed the formation of a range of disinfection by-products (DBPs) from the chloramination of seven non-nitrogenous LMWOA precursors, with an emphasis on the contribution of N-chloramine incorporation to haloacetamide (HAcAm) formation. The other DBPs comprised chlorinated halomethanes, haloacetonitriles and haloac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Generally, in the few samples that HANs were detected (pH 8), those yields were higher following chlorination and lower in chloramination than those of total HAcAm; with the exception of acetoacetamide. This pattern was in agreement with previous precursor studies of organic acids and natural organic matter solutions, that reported favouring of HAcAm formation via chloramination in the absence of bromide (Chu et al, 2016;Huang et al, 2017). In this study, of note, amide compounds at pH 7 generated undetectable levels of HANs upon chlorination, whereas upon chloramination TCAN (0.17 %M/M) was the only species at 24 hours in the β-alaninamide samples.…”
Section: Formation Of Nitrogenous Disinfection By-products (Hacams and Hans)supporting
confidence: 93%
See 2 more Smart Citations
“…Generally, in the few samples that HANs were detected (pH 8), those yields were higher following chlorination and lower in chloramination than those of total HAcAm; with the exception of acetoacetamide. This pattern was in agreement with previous precursor studies of organic acids and natural organic matter solutions, that reported favouring of HAcAm formation via chloramination in the absence of bromide (Chu et al, 2016;Huang et al, 2017). In this study, of note, amide compounds at pH 7 generated undetectable levels of HANs upon chlorination, whereas upon chloramination TCAN (0.17 %M/M) was the only species at 24 hours in the β-alaninamide samples.…”
Section: Formation Of Nitrogenous Disinfection By-products (Hacams and Hans)supporting
confidence: 93%
“…2b). It is noteworthy that when bromide was spiked at pH 7, HAcAm yields increased at least two-fold from those observed at pH 8, due to the increased stability at lower pH (Chu et al, 2016). Namely, acetamide samples under the same conditions generated 0.81% and 2.2% M/M upon chlorination, whereas generated 0.40% and 0.81% M/M upon chloramination, at pH 8 and 7 respectively.…”
Section: Bromide Addition In Amide Precursorsmentioning
confidence: 91%
See 1 more Smart Citation
“…The research work nowadays is oriented toward treatment of wastewater and drinking water from various organic contamination, more specifically from pharmaceuticals and personal care products. Amine-based pharmaceuticals such as nizatidine, ranitidine, doxylamine, and carbinoxamine have attracted most researchers’ attention because of the ability of these compounds to produce toxic nitrogenous disinfection by-products (NDMPs), which are formed during the disinfection step. , Unfortunately, in conventional wastewater treatment some NDMPs have been detected after applying commonly used oxidants such as chlorine, chlorine dioxide, and potassium permanganate. However, most of the recent studies focused on the occurrence of NDMP compounds and the potential risk on the environment resulting from such compounds. On the other hand, only few studies have been undertaken photocatalytic degradation of amine-based pharmaceuticals as an alternative way of wastewater treatment. , …”
Section: Introductionmentioning
confidence: 99%
“…Because of the occurrence and elevated toxicity of HANs and HAMs, there is an emphasis on research efforts to characterize their formation mechanism relevant in drinking waters. The formation of HANs and HAMs in drinking water has been hypothesized based on the origin of nitrogen atom in their molecule. Nitrogen-containing organic matter (i.e., amino acids, algal matter) could serve as a major precursor to form N-DBPs when it reacts with chlorine or chloramine via the decarboxylation pathway. On the other hand, the nitrogen atom of the nitrile group or the amide group of HANs or HAMs could also come from monochloramine, an inorganic source, reacting with aldehydes or aromatic compounds. ,,, All of these formation pathways may occur simultaneously and one pathway may become dominant at certain conditions. In two previous studies using 15 N-labeled-monochloramine, one reported >70% DCAN produced contained 15 N atom while the other demonstrated >92% of DCAN produced contained 15 N atom .…”
Section: Introductionmentioning
confidence: 99%